2013
DOI: 10.1080/10572317.2013.10766380
|View full text |Cite
|
Sign up to set email alerts
|

Library consortia in India with special reference to UGC-Infonet digital library consortium

Abstract: Including scholarly contents has given right to the publishers of peer-reviewed journals to keep higher subscription rates. It always affects library budget to a great extent. Since long libraries have been experimenting different ways of library cooperation so that maximum benefit, especially economic benefit, could be extracted from their joint cooperation ventures. The term 'consortia' has been considered an advanced stage of library cooperation. Advent of electronic journals has given rise to homogonous li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Goudar (2013) argues that development of library consortia in India was precipitated by the escalating prices of journals, the geometric growth of scholarly publishing and uncertain foreign exchange rates that put already shrinking budgets of Indian libraries in steep decline. In an endeavor to support research activities throughout the country and to avoid duplication of activities, the government of India launched a national information system called the National Information System for Science and Technology (NISSAT) in 1977 (Chauhan & Mahajan, 2013). NISSAT supported and sponsored resource-sharing activities by establishing library networks and consortia in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Goudar (2013) argues that development of library consortia in India was precipitated by the escalating prices of journals, the geometric growth of scholarly publishing and uncertain foreign exchange rates that put already shrinking budgets of Indian libraries in steep decline. In an endeavor to support research activities throughout the country and to avoid duplication of activities, the government of India launched a national information system called the National Information System for Science and Technology (NISSAT) in 1977 (Chauhan & Mahajan, 2013). NISSAT supported and sponsored resource-sharing activities by establishing library networks and consortia in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cooperation between the members is consistent with higher corporate objectives and values. Chauhan and Mahajan (2013) concluded that supervision of cooperation between institutions by one administrative entity is much easier than management of such cooperation by more than one administrative entity as in the former case a higher entity imposes legislations and laws governing the cooperative program and these become binding to the members.…”
Section: Benefits Of Cooperationmentioning
confidence: 99%
“…Their study showed the need for training the scholars in the use of e‐journals. Another study identifies the limitations and problems for low usage of these e‐resources at the Himachal Pradesh University and offers some suggestions to improve the usage (Chauhan et al , 2011). Swain and Panda (2009) have reported that e‐resources are used more as compared to CDROM databases by the faculty members of business schools in Orissa and Google and Yahoo are the most frequently used search engines.…”
Section: Usage Across Institutionsmentioning
confidence: 99%